Work-out und Servicing von notleidenden Krediten: Berichte und Referate des HfB-NPL Servicing Forums 2006 - Christoph Schalast; Klaas Ockens; Clemens J. Jobe; Robert Safran (HfB - Business School of Finance & Management, 2006)
The report deals with the current questions relating to the work-out, outsourcing and servicing of non-performing-loans. After a brief market description the paper addresses the specific problems, which arise when servicing real estate and corporate loans. Within these framework issues, which include banking secrecy rules, the risk of civil liability for banks in respect to non-performing-loans, banking regulation law, are explained and practical suggestions for a proposed line of action are made. The main objective is to identify the basic lines taken in the discussion so far and to define different approaches to the topic for the purposes of research and legal practice.
urn:nbn:de:101:1-20080827178
Keywords: K12; K19; K22; K29; 330; Non-performing-loans; distressed debt; portfolio-management; work-out; outsourcing; servicing; banking regulation law; bankers duty of secrecy; civil liability risks; corporate loans; real estate loans